Ciberadiccion y su impacto en el rendimiento académico de un estudiantes de sexto grado de la Unidad Educativa 10 de Noviembre - Rodriguez Suarez, Deysi Odalis (2022)
Internet addiction has become a very common problem, both children and adolescents who are the most likely to suffer from this addiction, have several consequences because of this vice, it is very important to take precautions in this situation to prevent a series of negative results , in this case study we seek to determine the relationship between cyber addiction and the impact it has on academic performance, the patient, being vulnerable, seeks refuge surfing the Internet because he sees it as his only means of distraction and way of fleeing From reality, a strong reason to start this study was because the family member states that the most worrying thing is that she has already requested about two school years previously, since at her age she should have already advanced to the 8th year of education, that is why used the descriptive research methodology, it is the con has direct contact with the evaluated, also using the correlational research that Helps determine the relationship between the two variables with a mixed approach. The techniques used below are: the structured interview, the clinical history and direct observation, through which the collection of information from the study subject will be carried out in order to proceed to apply the psychometric tests to measure their degree of addiction and as in their coping with this problem.